Transcriptome dynamics in Artemisia annua provides new insights into cold adaptation and de-adaptation - He, Yunxiao; Zhang, Yujiao; Li, Jiangnan; Ren, Zhiyi; Zhang, Wenjing; Zuo, Xianghua; Zhao, Wei; Xing, Ming; You, Jian; Chen, Xia (Frontiers in Plant Science, 2024)
Plants adapt to cold stress through a tightly regulated process involving metabolic reprogramming and tissue remodeling to enhance tolerance within a short timeframe. However, the precise differences and interconnections among various organs during cold adaptation remain poorly understood. This study employed dynamic transcriptomic and metabolite quantitative analyses to investigate cold adaptation and subsequent de-adaptation in Artemisia annua (A. annua), a species known for its robust resistance to abiotic stress. Our findings revealed distinct expression patterns in most differentially expressed genes (DEGs) encoding transcription factors and components of the calcium signal transduction pathway within the two organs under cold stress. Notably, the long-distance transport of carbon sources from source organs (leaves) to sink organs (roots) experienced disruption followed by resumption, while nitrogen transport from roots to leaves, primarily in the form of amino acids, exhibited acceleration. These contrasting transport patterns likely contribute to the observed differences in cold response between the two organs. The transcriptomic analysis further indicated that leaves exhibited increased respiration, accumulated anti-stress compounds, and initiated the ICE-CBF-COR signaling pathway earlier than roots. Differential expression of genes associated with cell wall biosynthesis suggests that leaves may undergo cell wall thickening while roots may experience thinning. Moreover, a marked difference was observed in phenylalanine metabolism between the two organs, with leaves favoring lignin production and roots favoring flavonoid synthesis. Additionally, our findings suggest that the circadian rhythm is crucial in integrating temperature fluctuations with the plant's internal rhythms during cold stress and subsequent recovery. Collectively, these results shed light on the coordinated response of different plant organs during cold adaptation, highlighting the importance of inter-organ communication for successful stress tolerance.